DEVELOPMENT OF TECHNOLOGIES OF SEMI-FABRICATES WITH USE OF PLANT ADDITIVES - Слободянюк, Наталья; Веретинська, Ирина (Modern engineering and innovative technologies, 2017)
seminal semifinished products, technology, flax seeds, components, food fibers, research.